242 Regional emergency care network for the management of acute myocardial infarction. Experience of RESURCOR in the French northern Alps. (23rd September 2015) - Belle, L; Chacornac, M; Ageron, F X; Hugon, V; Usseglio, P; Debatty, G; Labarere, J; Fourny, M; Rubio, C; Vanzetto, G
Abstract : Program: In 2002, the regional agency of health in Rhone-alps area set up a health care network with the goal to optimise patient management, by a better coordination of existing facilities in the northern Alps. The 'RESeau des URgences CORonariennes' (RESURCOR), a subgroup of this network, is in charge of urgent cardiac care. The RESURCOR involves three French departments: Isere, Haute-Savoie and Savoie, which includes 1.8 million people with wide seasonal variations related to tourism. It coordinates urgent care between one university hospital, 12 general and three private hospitals, three emergency medical aid departments (SAMU), 12 mobile intensive care units (SMUR) and four cardiac interventional units. Emergency physicians and interventional and non-interventional cardiologists meet regularly to set up regional procedures for the management of patients suffering from acute myocardial infarction. It highlights the importance of reperfusion techniques, delays to have reperfusion and where the patient has to be admitted. A permanent regional registry monitors the management of these patients, the types of management and time. Results: Since 2002, 3940 patients have been included in this registry. The accuracy was assessed at 84%. During the studying period, the number of primary percuntaneous interventions (PCI) gradually increased (33% in 2002 to 53% in 2008). The average time from the first medical contact to intravenous thrombolysis (62 mn in 2002 to 24 mn in 2008) and to arterial puncture of primary PCI (101 mn in 2002 to 78 mn in 2008) significantly decreased. Prehospital management by air increased from 3% in 2002 to 12% in 2008. According to the regional recommendations, 92% of the patients were directly admitted to an interventional coronary center in 2008. Discussion: RESURCOR submit recommendations for patient management and assess through a registry if the recommendations have been followed by physicians. Myocardial infarction was the first condition which the network took care of. Since this approach succeeded, we have followed the same pattern for the other diseases requiring cooperations between hospitals without the same technical equipment: Unstable angina, stroke (fibrinolysis sometimes required), cardiac arrest (urgent coronary angiography or extra corporeal membrane oxygenation sometimes required) and severe traumatology (trauma-system). Conclusion: RESURCOR is a network for patient management which needs urgent care. It allows coordination of care between different institutions in a large area. Objectif: Amélioration des prises en charge des infarctus du myocarde. Programme: En 2002, le RENAU (REseau Nord Alpin des urgences), réseau de prise en charge des urgences a été mis en place sur le Nord des Alpes, a l`initiative de l`Agence Régionale d`Hospitalisation. Au sein de ce réseau, la filière cardiologique s`est organisée autour du RESURCOR. Le RESURCOR couvre les départements de l`Isère, la Haute-Savoie et la Savoie, soit un total de 1.8 million d`individus, avec de larges variation saisonnières. Il concerne un CHU, 12 hôpitaux généraux, 3 cliniques privées, 3 SAMU, 12 SMUR et 4 centres de cardiologies interventionnelles. Le financement du réseau a permis de recruter 2 médecins responsables a temps partiels, une coordinatrice et 4 techniciennes de recherche cliniques a temps plein. Un site internet permet de faire circuler l`information et aux acteurs de communiquer (http://www.renau.org ). Urgentistes, cardiologues interventionnels et non interventionnels se réunissent régulièrement pour mettre a jour les recommandations régionales de prise en charge des infarctus du myocarde. Elles insistent sur l`importance des techniques de reperfusion, des délais de prise en charge et des parcours de soins des patients. Un registre régional a été mis en place en 2002 pour évaluer sur le terrain la qualité des prises en charges. Le registre définit pour tous les patients victimes d`infarctus aigu du myocarde, les techniques de reperfusions, les délais de prise en charge et les parcours des patients. Résultats: Depuis 2002, 3940 patients ont été inclus avec une exhaustivité mesurée a 84%. Le nombre annuel des inclusions est stable depuis 2002. On assiste dans le temps a une augmentation du nombre d`angioplasties primaires (33% en 2002 à 53% en 2008). Les délais de reperfusion diminuent significativement dans le temps avec un délai médian de thrombolyse passant de 62 mn en 2002 à 24 min en 2008 et un délai médian de ponction en angioplatsie primaire passant de 101 mn en 2002 à 78 min en 2008. Le nombre des prises en charges héliportées a significativement augmenté avec le temps (3% en 2002 et 12% en 2008). Selon les recommandations, 92% des patients sont adressés directement a un centre de cardiologie interventionnelle en 2008. Discussion: Le RESURCOR émet des propositions de prise en charge, définit des référentiels de bonne pratique et vérifie les modalités de prise en charge de ces urgence dans la pratique, à l`aide d`un registre continu, dédié a l`évaluation des pratiques professionnelles. L`infarctus du myocarde a été la première pathologie concernée par cette démarche et devant le succès obtenu, nous avons développé le même concept aux principales urgences pouvant nécessiter une collaboration entre les établissements de santé: L`angor instable (angioplastie coronaire), l`AVC (Thrombolyse), l`arrêt cardiaque (angioplastie coronaire, ECMO) et la traumatologie grave (Trauma-system). Conclusion: Le RESURCOR est un réseau de prise en charge, issu du terrain et finance par l`agence régionale d`hospitalisation. Il permet de coordonner et d`organiser la prise en charge des urgences a l`échelle d`un bassin important de population en faisant travailler ensemble des établissements avec des plateaux techniques hétérogènes.